Verification of Maman (Cleome gynandra (L.) Briq.) from Riau Based on matK and trnL-trnL-trnF Intergenic Spacer - Roslim, Dewi Indriyani; Herman, Herman; Putri, Shalsadila Rahmadani; Furqoni, Aries Tri; Budiono, Deanne Yoshe Fidela; Altuhaish, Adeel Abdulkarim Fadhl; Lestari, Wahyu (Biosaintifika: Journal of Biology & Biology Education, 2023)
Maman is a traditional plant frequently used as food by people in Melayu Rokan of Riau Province. Morphological detection indicates that the scientific name of maman is Cleome gynandra L.  The objective of this study is to confirm the taxonomic status of maman from Riau basedon matK and trnL-trnL-trnF intergenic spacer (IGS) sequences. Methods utilized in this study included sampling, DNA extraction, PCR, electrophoresis, sequencing, and data analysis. The fresh leaves were picked up from Rokan Hulu Regency, Riau Province. In this study, the matK and trnL-trnL-trnF IGS sequences of maman with a length of 754 bp and 938 bp, respectively, had been obtained. The BLASTn analysis based on both sequences showed that maman had 100% similarity to Gynandropsis gynandra. Cleome gynandra was synonymous with G. gynandra. There were 49 nucleotide variations, 16 critical nucleotides, and there were no indels in matK. Meanwhile, in trnL-trnL-trnF IGS there were 181 nucleotide variations, 13 critical nucleotides, and 61 indels. In conclusion, this study succeeded in confirming the taxonomic status of maman from Riau as C. gynandra syn. G. gynandra. The result enriched the abundance of DNA barcode sequences of this plant in GenBank which is useful for the molecular identification.